2021
DOI: 10.1111/vec.13147
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective evaluation of the relationship between admission variables and brain herniation in dogs (2010–2019): 54 cases

Abstract: Objective: To document the admission systolic blood pressure (SBP), heart rate (HR), and modified Glasgow coma scale (MGCS) score in dogs with and without brain herniation and to determine their relationship with brain herniation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…CR is a well-recognised ICP-related cardiovascular reflex; however, in human medicine, it is reported to have a low sensitivity for the detection of raised ICP. 10 Although, in dogs, higher BP and lower HR at admission have been associated with the presence of brain herniation, 11 this has not been seen in cats. 12 A retrospective study in cats undergoing surgical removal of intracranial meningioma reported the absence of CR in some patients where raised ICP was confirmed by continuous monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…CR is a well-recognised ICP-related cardiovascular reflex; however, in human medicine, it is reported to have a low sensitivity for the detection of raised ICP. 10 Although, in dogs, higher BP and lower HR at admission have been associated with the presence of brain herniation, 11 this has not been seen in cats. 12 A retrospective study in cats undergoing surgical removal of intracranial meningioma reported the absence of CR in some patients where raised ICP was confirmed by continuous monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a similar study conducted in dogs, 11 our hypothesis was that a Cushing reflex will likely be exhibited in cats with brain herniation. Our hypothesis was not supported by the current study.…”
Section: Discussionmentioning
confidence: 99%
“…11 While the presence of the Cushing reflex in cats in the clinical setting appears to be limited, it is important to note that the Cushing reflex may be a late sign of increased ICP. 4,6,11,20 Therefore, relying on the Cushing reflex to make treatment decisions may lead to a worse outcome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations